Mid‐term outcome of endoscopic sphincterotomy combined with large balloon dilation. Issue 1 (January 2015) - Itokawa, Fumihide; Itoi, Takao; Sofuni, Atsushi; Kurihara, Toshio; Tsuchiya, Takayoshi; Ishii, Kentaro; Tsuji, Shujiro; Ikeuchi, Nobuhito; Umeda, Junko; Tanaka, Reina; Tonozuka, Ryosuke; Honjyo, Mitsuyoshi; et al.
Abstract Background and Aim Endoscopic sphincterotomy (ES) combined with large balloon dilation (ESLBD) can be useful for extracting large and multiple bile duct stones. Although there are many studies on the feasibility and short‐term outcome, there are few reports about mid‐ to long‐term outcome after ESLBD. The aim of our study is to prospectively evaluate the mid‐term outcome of ESLBD. Methods One hundred eighty‐three patients who underwent ESLBD between November 2006 and May 2012 were included. The patients were followed up periodically after the procedure until April 2013. Papillary dilation was performed at the time of initial ES or prior ES. Early and late adverse events and stone recurrence were evaluated in this study. Results The patients' mean age was 76.6 ± 10.7 years. Surgically altered anatomy was present: Billroth I gastrectomy (2), Billroth II gastrectomy (13), and gastrectomy with Roux‐en Y reconstruction (18). Seventy‐eight (42.6%) patients had periampullary diverticulum. Prior ES had been performed in 40 (21.9%) patients. The mean follow‐up period was 43.5 ± 19.7 months (range 11–78). Eight (4.4%) patients had stone recurrence. There was rare stone recurrence after initial ESLBD treatment and native gastrointestinal anatomy. Univariate and multivariate analyses showed that prior ES and previous history of stone recurrence were predictive of stone recurrence (P < 0.001). Conclusion At mid‐term outcome, ESLBD is associated with a low rate of recurrent bile duct stones, although long‐term follow up is needed.